Caulobacter soli sp. nov., isolated from soil sampled at Jiri Mountain, Republic of Korea. Issue 7 (11th July 2020) - Yang, Yuanyuan; Jin, Chun-Zhi; Jin, Feng-Jie; Li, Taihua; Lee, Jong-Min; Kim, Chang-Jin; Lee, Hyung-Gwan; Jin, Long
Abstract : A Gram-stain-negative, yellow-pigmented, aerobic, non-spore-forming, motile with a single polar flagellum and rod-shaped bacterium, Ji-3-8 T, was isolated from a soil sample taken from Jiri Mountain, Republic of Korea. Comparative 16S rRNA gene sequence studies showed the isolate had clear affiliation with Alphaproteobacteria and the closest relatedness to Caulobacter rhizosphaerae KCTC 52515 T, Caulobacter henricii ATCC 15253 T, Caulobacter segnis ATCC 21756 T, Caulobacter hibisci THG-AG3.4 T, Caulobacter flavus RHGG3 T and Caulobacter vibrioides CB51 T showing 99.1, 98.9, 97.7, 97.6, 97.5 and 97.4 % 16S rRNA gene sequence similarity, respectively, and 94.7–96.5 % to the remaining species of genus Caulobacter . The predominant ubiquinone was Q-10 and the major fatty acids were C18 : 1  ω 7 c 11-methyl, C16 : 0, summed feature 8 (C18 : 1  ω 6 c and/or C18 : 1  ω 7 c ) and summed feature 3 (C16 : 1   ω 6c and/or C16 : 1  ω 7 c ). The major polar lipids were found to be phosphatidylglycerol, two unidentified phosphoglycolipid and two unidentified glycolipids. The G+C content of the genomic DNA of strain Ji-3-8 T was 68.1 mol%. Average nucleotide identity and digital DNA–DNA hybridization values of strain Ji-3-8 T with C. rhizosphaerae KCTC 52515 T, C. henricii ATCC 15253 T, C. segnis ATCC 21756 T, C. flavus RHGG3 T and C. vibrioides were 79.7–87.7% and 23.0–34.3%, respectively. Based on the polyphasic evidence, it is proposed that strain Ji-3-8 T forms a novel species in the genus Caulobacter, for which the name Caulobacter soli sp. nov. is proposed. The type strain is Ji-3-8 T (=CCTCC AB 2019389 T =KCTC 72990 T ).